Effect of impact assembly on the interface deformation and fretting corrosion of modular hip tapers: An in vitro study. Issue 1 (26th June 2017) - Panagiotidou, Anna; Cobb, Timothy; Meswania, Jay; Skinner, John; Hart, Alister; Haddad, Fares; Blunn, Gordon
ABSTRACT: Wear and corrosion at the modular head–neck junction has been recognised to be a potential clinical concern, with multiple reports on adverse local tissue reactions and subsequent early failure of metal‐on‐metal hip replacements. Furthermore, reports on head–neck taper corrosion are also being described with conventional metal‐on‐polyethylene bearings. Manufacturing tolerances, surgical technique, non‐axial alignment, material combination, high frictional torque and high bending moment have all been implicated in the failure process. There is limited guidance on the force of impaction with which surgeons should assemble modular hip prostheses. This study aims to investigate the effect of impaction force on the deformation and corrosion of modular tapers. Short neck tapers with high surface roughness (average R z = 16.58 μm, R a = 4.14μm) and long neck tapers with low surface roughness (average R z = 3.82 μm, R a = 0.81μm), were assembled with CoCrMo alloy heads (smooth finish) under controlled conditions with 2, 4 or 8 kN of impaction force. Material combinations tested included CoCrMo‐head/CoCrMo‐neck and CoCrMo‐head/Ti‐6Al‐4V‐neck. Assessment of surface deformation before and after impaction was made using surface profilometry. Measurement of fretting current during sinusoidal cyclic loading evaluated mechanically assisted corrosion for each assembly load during short‐term cyclic loading (1000‐cycles) and long‐term cyclic loading (5 million‐cycles). Deformation on head and neck tapers increased with assembly load. Fretting currents during short term simulation testing showed significantly lower currents ( p < 0.05), in 8 kN assemblies when compared to 2 and 4 kN, especially for the short‐rough tapers. Long‐term simulator testing demonstrated a progressive reduction in fretting corrosion for samples impacted with 4 and 8 kN; however, this reduction was greater for samples impacted at 8 kN even at the start of testing. Based on our results, surgeons could minimise mechanically assisted crevice corrosion by using higher impact loads when assembling the head to the stem in total hip arthroplasty. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:405–416, 2018.